AB0917 Pulmonary Manifestations in Patients with IGG4-Related Disease at A Tertiary Care Institute. (15th July 2016) - Banka, R.; Gc, Y.; Balakrishnan, C.; Samant, R.; Pinto, L.; Sagdeo, P.S.
Abstract : Background: IgG4-Related Disease (IgG4 RD) is a rare immune-mediated disease with multi-organ involvement. Objectives: To describe pulmonary manifestations of patients with IgG4-RD. Methods: Chart review was performed of consecutive patients diagnosed with IgG4 RD between 2009–2014 at the PD Hinduja National Hospital, Mumbai. Included patients fulfilled diagnostic criteria of Japanese Ministry of Health, Labour and Welfare guidelines, 2011.Their clinical features, laboratory findings were noted down. Results: 8 of 11 patients with IgG4 RD had pulmonary manifestations. Ages of presentation ranged from 15–73 years.6 patients were female. Average delay in diagnosis was 9 months. Prior to diagnosis, 3 patients received empiric antituberculous drugs and bronchoalveolar lavage performed in 3 patients was non-diagnostic. The right mainstem bronchus was found to be narrowed in 1 patient. The serum IgG4 levels were elevated in all patients. Median IgG4 level was 4.76 mg/dl (IQR 3.26, 6.1).Presenting symptoms, thoracic CT and histopathological findings are summarized below Conclusions: Pulmonary involvement in IgG4 RD is common and should be sought for in patients diagnosed with the disease. References: Umehara, H. et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Mod. Rheumatol. 22, 21–30 (2012). Disclosure of Interest: None declared